2014
DOI: 10.1016/j.egypro.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Development of 2nd Generation Oxyfuel CFB Technology – Small Scale Combustion Experiments and Model Development Under High Oxygen Concentrations

Abstract: The 1 st generation oxyfuel CFB (Circulating Fluidised Bed) technology has been demonstrated up to 30MW th scale and the commercial concept for 300 MW e air/oxy flexible CFB power plant is available. Currently, the development of 2 nd generation oxyfuel CFB technology is ongoing aiming to reduce significantly -around 50% -the overall efficiency penalty of CO 2 capture in power plants compared to 1 st generation concepts. The 2 nd generation oxyfuel CFB plants are designed only to oxyfuel operation with CCS.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…With both tested fuels (bituminuos coal and anthracite), the temperature level is slightly lower in 21%O 2 /79%CO 2 mixture than in air and the temperature increases as the oxygen concentration increases. Similar results were reported by Jang et al (2014b) for a 30 kWth unit combusting sludge and by Pikkarainen et al (2014) for a 100 kWth unit combusting mixture of anthracite and petroleum coke. Fig.…”
Section: Heat Transfersupporting
confidence: 92%
See 3 more Smart Citations
“…With both tested fuels (bituminuos coal and anthracite), the temperature level is slightly lower in 21%O 2 /79%CO 2 mixture than in air and the temperature increases as the oxygen concentration increases. Similar results were reported by Jang et al (2014b) for a 30 kWth unit combusting sludge and by Pikkarainen et al (2014) for a 100 kWth unit combusting mixture of anthracite and petroleum coke. Fig.…”
Section: Heat Transfersupporting
confidence: 92%
“…In their pilot scale tests, a real recycled flue gas is used. Their tests indicated that both indirect and direct mechanisms have been observed during the oxyfuel combustion campaigns (Pikkarainen et al, 2014).…”
Section: Understanding Of Sulphur Capture During Oxy-cfb Combustion -mentioning
confidence: 98%
See 2 more Smart Citations
“…Fluidised bed combustion has long been applied as a flexible means to burn biomass. Oxy-fuel circulating fluidized bed combustion technology has been under development [2]. The combustion is achieved in a mixture of oxygen and recirculated flue gases instead of air and the flue gases consist of carbon dioxide and water vapour allowing CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%